The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s00296-018-3988-2
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage turnover and intra-articular corticosteroid injections in knee osteoarthritis

Abstract: Intra-articular corticosteroid injections (IACI) are commonly used interventions for pain relief in patients with knee osteoarthritis (OA). Biomarkers may be helpful in further elucidating how IACI exert their effect. The aim of this study is to look at the response of biomarkers of cartilage and bone metabolism after IACI in knee OA. Eighty subjects with symptomatic knee OA [45% male, mean age (SD) 64 (11) years] underwent routine knee joint injection with 40 mg triamcinolone acetonide and 4 ml 1% lignocaine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
0
27
1
Order By: Relevance
“…16 This is the first study of a placental-derived injection for OA; however, these results compare favorably to other studies evaluating single IA injections, including a high-molecular-weight HA (58.9% for HA, 51.2% for saline at 26 weeks) 17 and a cross-linked HA (61.0% for HA, 54.6% for saline at 13 weeks). 18 IA injections for OA include a variety of therapies including steroids, 11,19,20 HA, 19,21,22 PRP, [23][24][25] bone marrow aspirate concentrate (BMAC), 24,26 adipose-derived mesenchymal stem cells (AD-MSCs), 27 and autologous protein solution (APS), 28 with varying levels of supporting evidence. In this study, we focused on HA and saline as comparators to ASA for treatment of OA.…”
Section: Discussionmentioning
confidence: 99%
“…16 This is the first study of a placental-derived injection for OA; however, these results compare favorably to other studies evaluating single IA injections, including a high-molecular-weight HA (58.9% for HA, 51.2% for saline at 26 weeks) 17 and a cross-linked HA (61.0% for HA, 54.6% for saline at 13 weeks). 18 IA injections for OA include a variety of therapies including steroids, 11,19,20 HA, 19,21,22 PRP, [23][24][25] bone marrow aspirate concentrate (BMAC), 24,26 adipose-derived mesenchymal stem cells (AD-MSCs), 27 and autologous protein solution (APS), 28 with varying levels of supporting evidence. In this study, we focused on HA and saline as comparators to ASA for treatment of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of joint fluid for biomarker analysis even in the dry (non-effusive) knee is presently an important area in arthritis research and may also be integral to future joint preservation strategies and therapies [6,22,29,30]. Similar to Bhavsar et al, Yaqub et al, and Meehan et al, but using a different study design, we found that mechanical compression permitted fluid extraction in a much greater proportion of osteoarthritic knees that presented clinically as dry, non-effusive knees (Figure 3) [7-9].…”
Section: Discussionmentioning
confidence: 99%
“…After non-pharmacologic interventions and topical and oral medications, complete arthrocentesis followed intraarticular injection of corticosteroids is often recommended for symptomatic flares and short-term relief of pain of arthritis of the knee [1-5]. Klocke and colleagues have recently reported that corticosteroid injection of the osteoarthritic knee may actually decrease cartilage degradation in the short-term as measured by biomarkers, providing indirect support for the above recommendations [1-6]. Recently, Meehan et al, Bhavsar et al, and Yaqub et al have demonstrated that mechanical compression of the knee provides more complete arthrocentesis before injection in both the effusive and non-effusive knee and suggest that mechanical compression might be a reasonable quality improvement intervention for arthrocentesis [6-9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type IIA (PIIANP) contains exon 2 and is expressed by chondroprogenitor cells, whereas type IIB (PIIBNP) is devoid of exon 2 and is expressed in differentiated chondrocytes [ 21 23 ]. Although Sharif reported that serum PIIANP in knee OA progressors was higher than that in OA non-progressors [ 24 ], most of the previous studies have demonstrated that serum PIIANP decreased in knee OA patients compared to controls [ 25 30 ]. PIIBNP is believed to be the only procollagen expressed during the formation of type II collagen in healthy adult human cartilage [ 31 ].…”
Section: Discussionmentioning
confidence: 99%